Profil penggunaan obat antidiabetes pada pasien diabetes mellitus tipe 2 di instalasi rawat jalan RSUD Provinsi NTB tahun 2018 - Baiq Sofianti Annisa; Candra Eka Puspitasari; Siti Rahmatul Aini (Sasambo Journal of Pharmacy, 2021)
Diabetes mellitus (DM) is a disorder of insulin secretion, insulin action or both, which are characterized by blood glucose levels > 200 mg/dl and / or fasting blood glucose levels > 126 mg/dl. In 2017 Indonesia was recorded as the sixth largest country with DM in the world. The most common classification of diabetes is type 2 DM with an incidence 90-95%. The study aimed to determine the profile of antidiabetic use in type 2 DM patients at the outpatient installation of RSUD Provinsi NTB in 2018. This study used cross sectional design retrospectively with purposive sampling method for the period January-December 2018. The results showed that in 112 patients, 195 antidiabetic agents were prescribed. The antidiabetic prescribed were metformin (33.85%), glimepirid (25.13%), aspart insulin (13.33%), insulin detemir (8.21%), pioglitazone (6.67%), insulin glargine (6.67%), glyclazide (1.54%), gliquidone (1.54%), acarbose (1.54), regular insulin (1.03%), and insulin lispro (0.51%). Overall, antidiabetic use was in accordance with the guideline recommendations. Further research is needed regarding the review of prescriptions and detailed indications in order to increase rationality of drug use, reduce morbidity and mortality and reduce medical costs.